An Interview with Tony Zanders, Founder of Skilltype. Issue 1 (17th August 2020) - Cook, Eleanor I.; Zanders, Tony
ABSTRACT: This interview with Tony Zanders focuses on a product he is building that will assist libraries and information professionals with job skill analysis and development, with the goal of "future-proofing" the professions in this realm. Skilltype is a platform that will assist with "analyzing, developing and sharing expertise" so that libraries and other information centers can make the most of their workforce.